A national assessment of the utilization, quality and cost of laparoscopic liver resection. Issue 10 (October 2019) - Gani, Faiz; Ejaz, Aslam; Dillhoff, Mary; He, Jin; Weiss, Matthew; Wolfgang, Christopher L.; Cloyd, Jordan; Tsung, Allan; Johnston, Fabian M.; Pawlik, Timothy M.
Abstract: Background: Despite recent enthusiasm for the use of laparoscopic liver resection, data evaluating costs associated with laparoscopic liver resections are lacking. We sought to examine the use of laparoscopic liver surgery, and investigate variations in cost among hospitals performing these procedures. Methods: A nationally representative sample of 12, 560 patients who underwent a liver resection in 2012 was identified. Multivariable analyses were performed to compare outcomes associated with liver resection. Results: Among the 12, 560 patients who underwent liver resection, 685 (5.4%) underwent a laparoscopic liver resection. The proportion of liver resections performed laparoscopically varied among hospitals ranging from 4.6% to 20.0%; the median volume of laparoscopic liver resections was 10 operations/year. Although laparoscopic surgery was associated with lower postoperative morbidity (aOR = 0.60, 95%CI: 0.36–0.99) and shorter lengths of stay [(LOS) aIRR = 0.83, 95%CI: 0.70–0.97], it was not associated with inpatient mortality (p = 0.971) or hospital costs (p = 0.863). Costs associated with laparoscopic liver resection varied ranging from $5, 907 (95%CI: $5, 140-$6, 674) to $67, 178 (95%CI: $66, 271-$68, 083). The observed variations between hospitals were due to differences in morbidity (coefficient: $20, 415, 95%CI: $16, 000-$24, 830) and LOS (coefficient: $24, 690, 95%CI: $21, 688-$27, 692). Conclusions: Although laparoscopic liver resection was associated with improved short-term perioperative clinical outcomes, utilization of laparoscopic liver resection remains low.